Students’ creative thinking skills in solving PISA-like mathematics problems related to quantity content - Shalshabilla Shafa; Zulkardi Zulkardi; Ratu Ilma Indra Putri (Universitas Hamzanwadi, 2023)
The introduction of the Merdeka curriculum mandates that teachers emphasize the development of creative thinking abilities and incorporate learning into local contexts. For this reason, this study aims to describe the creative thinking skills of class VII students in answering PISA-like mathematics problems on quantity in the context of Palembang tourism using the Pendidikan Matematika Realistik Indonesia (PMRI) approach. This study used a descriptive study with 28 students from junior high school number 26 in Palembang. Tests, interviews, and observations were used to collect data. The analytical method used is descriptive. The PMRI technique learning is carried out in this study by providing student worksheets. The task of students to discuss each other's problems with different levels of difficulty, followed by two PISA-like mathematics problems in quantity content and the context of Palembang tourism. The results showed that students' average creative thinking skills were at a moderate level, with fluency and elaboration indicators appearing the most. However, only a few students have indicators of originality. Overall, the creative thinking ability of grade VII students in answering PISA-like mathematics problems in the quantity content and Palembang tourism by utilizing the PMRI approach is good because students can imagine questions because they use content and contexts that they have experienced.